Evaluation of the efficiency of the biological agent Trichoderma longibrachiatum and some chemical fungicides in inhibiting the pathogens of inflorescence rot of date palm in the laboratory - Mahdi, Basil Yousif; Al-Waiely, Dhiaa Salim (Basrah Journal Of Date Palm Research, 2024)
This study aimed to test the efficiency of the biological agent Trichoderma longibrachiatum and some chemical pesticides in inhibiting some pathogens that cause the date palm inflorescence rot in the laboratory. The fungus M. scaettae and some species belong to Fusarium spp. were isolated, including F. solani, F. oxysporum and F. moniliforme. The fungus Alternaria alternata was also isolated from infected palm pollen in some palm groves in Basrah Governorate. The fungi were diagnosed morphologically and tested their pathogenicity. The results showed that F. oxysporum and M. scaettae showed the highest degree of infection severity and the highest percentage of yield loss, reaching 90.92% and 84.01%, respectively, with a significant difference from the treatment of F. solani and A. alternata, which showed moderate infection severity and a percentage of yield loss of 42.7% and 33.77%, respectively, while the treatment of F. moniliforme gave the lowest degree of infection severity and the percentage of yield loss was 16.04%.. The antagonistic efficiency of the fungus T. longibrachiatum was also tested and the results showed that it has high efficiency against fungi species that cause the inflorescence rot disease. The effect of three concentrations (25%, 50% and 100%) of the recommended doses of five types of chemical pesticides on the inhibition of pathogens was studied: Ortiva Top, Goldazim, Brik, Pilarhymex and Bravo. The highest inhibition rate of pathogenic fungi was achieved when treated with Ortiva Top which achieved of 92.76%, followed by Brik pesticide treatment at an inhibition rate of 90.99%, while the treatment of pesticides, Pilarhymex and Goldazim recorded an inhibition rate of 87.03% and 85.97%, respectively. The lowest inhibition rate was achieved when treated with Bravo pesticide at 81.13%.